Values of heart rate variability indices recorded under conditions of active orthostasis for elite ski racers, as a reflection of sports vagotonia - D. A. Kataev; V. I. Tsirkin; A. N. Trukhin; S. I. Trukhina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In order to indirectly prove the nature of sports vagotonia, an analysis of 15 indicators of heart rate variability (HRV) was performed, recorded using the VNS-Micro system (Neurosoft, Ivanovo) by 5-minute cardiointervalography (CIG) under conditions of active orthostasis (ortho-CIG, ortho-HRV) at the 8 elite cross-country skiers (MS, MSMC) of the team of the Republic of Tatarstan during the preparatory and competitive periods, as well as a member of this team, athlete K.D. (MS, the first author of the article), whose ortho-CIG registration was carried out during the transition period. It was found that elite skiers in all three periods (especially in the preparatory and competitive periods) are characterized by high median values of such ortho-HRV indices as TP, AMVLF, pNN50%, RRNN, RMSSD, SDNN, MxDn, and low median values of HR and SI., which, judging by the literature data, are significantly they differ from the ortho-KIG of nonathletes, novice skiers, and representatives of other sports not related to endurance development. It is concluded that sports vagotonia is detected not only during the registration of clino-HRV, but also during the registration of ortho-HRV; it is due to the high level of activity of the parasympathetic division of the autonomic nervous system and, probably, the presence of synthesis of non-neuronal acetylcholine by cardiomyocytes.